Improving the Students' Recount Text Writing Achievement by Using Spidergram Technique at SMP Negeri 2 Tanggul - Pratiwi, Melinda; Suharjito, Bambang; Sukmaantara, I Putu (Jurnal Edukasi, 2014)
The purpose of this research was to solve the problems dealing with the students' active participation and writing achievement. The research design was Classroom Action Research. The area and subjects of this research were chosen purposively by using purposive method. The subjects were the VIII-D students at SMP Negeri 2 Tanggul in the 2013/2014 academic year. The data collected were writing test, observation, interview and documentation. The results of this research showed that there were improvement of students' participation and their writing achievement in Cycle 1 to Cycle 2. In Cycle 1, there were 54.05% of the students who actively participated during the teaching learning process. Meanwhile, there were 40% of the students who achieved the target score. Beside, in Cycle 2, there were 70.26% of the students who actively participated during the teaching learning process, while 70.27% of the students achieved the target score. It proved that the use of Spidergram technique could improve the students' active participation and writing achievement. Keywords : Active Participation, Classroom Action Research, Spidergram Technique, Writing Achievement.